Análise e uso da informação em pequenas empresas de base tecnológica incubadas no pólo tecnológico de São Carlos - SP - Periotto, Caroline (Universidade Federal de São Carlos, 2010)
The highly competitive global market environment, the recent technological advances, the importance of information as well as the volume of this information are responsible for the rapid changes in business enterprises, especially in the small businesses. In such market environment, the technology-based small enterprises (TBSE s) have excelled in incorporating innovation, strategic management of resources, generation of qualified jobs and salaries higher than the national average. It is necessary, however, to guarantee the maintenance of such competitiveness keeping in view their specificity in being small businesses and the fact that they face obstacles in their growth and consolidation. The analysis and adequate use of information offers an alternative to improve the position of these enterprises in the market and to procure new technologies helping them in their decision-taking processes. With these facts as the background, this work took, as its main objective, to study the manner in which the TBSE s analyze and use information and to propose a method based in the processes of decision-taking and competitive intelligence. Given the importance of the technology-based small enterprises, two groups of nascent enterprises of the Pólo Tecnológico de São Carlos, incubated in the São Carlos High Technology Park Foundation (ParqTec): (i) 15 enterprises belonging to the CINET/SOFTNET incubator of which four were generated by the Grants Program for the Development of New Enterprises with an Agricultural and Livestock Technology Base (PROETA); and (ii) 10 enterprises implanted in the Design Inn incubator. Data were collected from primary and secondary sources which served as the basis for the theoretical constructions of this study. These data lead to the results on: (i) Identification of characteristics and specificities of the investigated enterprises; (ii) Identification of the access and the use of information by the incubated TBSE s; (iii) Integration of a simplified method for the analysis and use of information based on the processes of decision-taking and competitive intelligence considering their specificities and the Brazilian realities, in such a way as to potentialize their improvement in the local decision processes and intelligence enhancement leading also to their consolidation and growth. The managers of TBSE s reflected on the questions raised about the information management and showed themselves receptive to the ideas. 72% of the managers perceived themselves to be motivated to adopt the information management process and 64% considered the process as a viable support system for decision-taking. It is hoped that the dissemination of the results of this study shall contribute toward the advancement of the knowledge and attitude of these enterprises in search for a competitive edge in the market and consequently toward the regional socioeconomic development.
Analysis and use of information in technology-based small enterprises incubated in the technological pole of São Carlos - SP
Keywords: Desenvolvimento social - ciência, tecnologia e sociedade; Gestão da informação; Inteligência competitiva; Análise da informação; Pólo tecnológico; Empresas de base tecnológica; Uso da Informação; Information Analysis; Information Use; Competitive intelligence; Information management; Technology based enterprises; Technology poles; Incubated enterprises; CIENCIAS SOCIAIS APLICADAS